Medicinal plants available in local markets contaminated with human pathogenic bacteria - Bacillus cereus and Pseudomonas gessardii (Asian Journal of Medical and Biological Research, 2022)
Medicinal plants are known to be a potential source of therapeutic aids. Different uses of medicinal plants have attained a powerful role in health system throughout the world. To study the microbial risk factor associated with medicinal plants, medicinal plant and part of plant samples (10 from each location) were collected from three different local markets (Nabinagar, Amin Bazar, and Savar) of Savar area, Dhaka, Bangladesh. A total number of fifty five (55) bacterial isolates have been isolated through their growth on Nutrient Agar media. Out of 55 isolates 31 isolates (56%) were identified as Bacillus cereus and 7 isolates (13%) were identified as Pseudomonas sp. through different morphological and biochemical tests. The CFU value of different samples revealed that all the values were higher than the accepted value (recommended by WHO, 2007) of 105 CFU/g except Phyllanthus emblica. The PCR and 16S rRNA sequencing confirmed the identification similarity values among two isolates of B. cereus and Pseudomonas gessardii. Both B. cereus and Pseudomonas gessardii showed sensitivity to the antibiotics Kanamycin, Gentamycin, Tigecycline, Ciprofloxacin and Amikacin where resistance to the antibiotics Amoxycilin, Aztreonam, Penicillin-G, Cefixime, Cefotaxime, Cefepime, Ceftriaxone, Meropenem, Cotrimoxazole and Ceftazidime. Therefore, quality assessment of herbal medicines should be ensured to make them safer for human consumption.Asian J. Med. Biol. Res. 2022, 8 (2), 69-78